1997
DOI: 10.1007/s002800050711
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of oncogenic ras- p21 in vivo by agents that block its interaction with jun -N-kinase (JNK) and jun proteins. Implications for the design of selective chemotherapeutic agents

Abstract: We have obtained evidence that oncogenic and activated normal ras-p21 proteins utilize overlapping but distinct signal transduction pathways. Recently, we found that ras-p21 binds to both jun and its kinase, jun kinase (JNK). We now present evidence that suggests that oncogenic but not normal activated p21 depends strongly on early activation of JNK/jun. This early activation most likely involves direct interaction between oncogenic p21 and JNK/jun because p21 peptides that blocked the binding of p21 to JNK an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Other compounds, including JNK interacting protein-1 ( Lee et al, 1999), specific JNK inhibitor (Amar et al, 1997), and mitogen-activated protein kinase phosphatase-1 (Laderoute et al, 1999), that have been reported to affect c-Jun phosphorylation or inhibit c-Jun kinase have a potential role as antifibrotic agents if they can be targeted to the fibrotic organ of interest. An inhibitory effect on the c-Jun-mediated pathway may explain the antiproliferative and antifibrotic activity of other compounds, including losartin (Varo et al, 1999), pirfenidone (Raghu et al, 1999), enalapril (Peters et al, 1998), octreotide (Fort et al, 1998a), captopril (Uhal et al, 1998), terbinafine (Ricard-Blum et al, 1998), interferon-␣ (Fort et al, 1998b), and pentifylline (Saika et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds, including JNK interacting protein-1 ( Lee et al, 1999), specific JNK inhibitor (Amar et al, 1997), and mitogen-activated protein kinase phosphatase-1 (Laderoute et al, 1999), that have been reported to affect c-Jun phosphorylation or inhibit c-Jun kinase have a potential role as antifibrotic agents if they can be targeted to the fibrotic organ of interest. An inhibitory effect on the c-Jun-mediated pathway may explain the antiproliferative and antifibrotic activity of other compounds, including losartin (Varo et al, 1999), pirfenidone (Raghu et al, 1999), enalapril (Peters et al, 1998), octreotide (Fort et al, 1998a), captopril (Uhal et al, 1998), terbinafine (Ricard-Blum et al, 1998), interferon-␣ (Fort et al, 1998b), and pentifylline (Saika et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…We then injection GST-pi into oocytes either together with oncogenic ras-p21 or into oocytes that were then incubated with insulin and found that GST-pi completely blocked oncogenic ras-p21-induced oocyte maturation but had no effect on the ability of insulin to induce oocyte maturation [56]. Co-injection of either cloned, purified JNK or jun together with oncogenic ras-p21 into oocytes results in a much more rapid induction of maturation than either agent alone while injection of either protein into oocytes that were then incubated with insulin showed not only no enhancement of the rate of maturation but a decrease in this rate [56].…”
Section: A Oncogenic Ras-p21 Interacts Selectively With Jnk and Junmentioning
confidence: 99%
“…Third, co-injection of JNK with Val 12-p21 results in a synergistic enhancement of oocyte maturation while injection of JNK or jun into insulin-treated oocytes results in a diminution of maturation (50). If activated cellular wild-type ras-p21 interacted with JNK in the same manner as the oncogenic protein, enhanced maturation should have been observed.…”
Section: Studies Further Confirm That Oncogenic Ras-p21mentioning
confidence: 99%